Formação continuada de professores: transtorno do processamento sensorial e as consequências para o desempenho escolar - Souza, Joana Rostirolla Batista de (Universidade Federal de São Carlos, 2014)
The Sensory Processing Disorder (SPD) can cause difficulties on scholar performance and behavior problems in this context, what may interfere, thus, on the full participation of the student. The teachers are on a ideal position for the recognizing of de disorder signs and can change the life of a lot of children, because the SPD are unkown in Brazil and doesn t find the diagnosis, those children must be helping the improve of the school failure statistics. On the international tendencies for the concept of inclusive education, the prepared teacher for the inclusion is that one capacitated for different pedagogic strategies, for different students. The further teacher development has been considered one of the better ways for prepare the teacher for the inclusion. The aim of this research was to evaluate the results (short and long-term) of a further teacher development intervention about the SPD and its consequences for the scholar performance. The method was exploratory-descriptive s qualitative and quantitative. The research received authorization of the Municipal Education Secretary, was approved by CEP and authorized by the school after the teacher approval. The data collection and intervention was developed in a classroom of the participant school, located on a peripheral region of a midsize city of São Paulo s State central region. The research steps where developed during six HTPC s moments (a time for pedagogic collective work) and the participants where 16 teachers and administrators responsible for the first to the fifth grade from a government college of elementary education. A pilot study previously developed with two volunteers embased the elaboration and adequation of the data collection instruments and the illustrative cases, which were used as a base for complete the instruments. For the initial collect, participants filled the self-guided interview and the pre-test sheet. After the intervention, they filled the course evaluation and the pos-test. Eight months later, it was developed the follow-up data collecttion individual for those whom cited current students with similar profiles to the illustrative cases and a general instrument for all the participants. The qualitative data analysis where realized by theoretical axis, the quantitative data where analised using the t-student test, adopting p<0,05. The results shown the effectiveness of intervention to form opinion about new and unknown topics, once it was a movement from the non-responded affirmatives to the ones correctly responded on the pos-test. However, the intervention wasn t able to modifies pre-established incorrect concepts from the initial data collection. The follow-up showed that, for the topic discussed on this constructed intervention, this kind of further development wasn t able to transform participants in prevention e action agents. That means that the further development of this research got positive short-term results, but not long-term outcome in respect to the changing attitude.
Further teacher development: sensory processing disorder and the consequences for de scholar performance
Keywords: Formação continuada de professores; Teoria da integração sensorial; Rendimento escolar; Problemas de comportamento; Transtorno do processamento sensorial; Further teachers development; Sensory integration theory; Sensory processing disorder; Difficulty in school performance; Problem of school behavior; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO::EDUCACAO ESPECIAL